2018
DOI: 10.1002/aocs.12013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (R)‐ and (S)‐Ricinoleic Acid Amides and Evaluation of Their Antimicrobial Activity

Abstract: A series of fatty acid amides derived from (R)‐ and (S)‐ricinoleic acid and 4 cyclic and acyclic amines were synthesized in a proecological solvent‐free process with yields ranging from 43 to 88%. All S‐configured compounds and both enantiomers of amide with 2‐amino‐2‐methyl‐1‐propanol were obtained and studied in terms of biological activity for the first time. The evaluation of antimicrobial activity of (R)‐ and (S)‐ricinoleic acid derivatives against 13 different microorganisms representing Gram‐negative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It was confirmed by our previous study, in which different (R)-and (S)-RA amides and their acetates were synthesized and examined in terms of anticancer and antimicrobial activity. The tested compounds exhibited significant pharmacological potential, and what is more, differences in the activity of the opposite enantiomers were observed in some cases (Matysiak et al 2017(Matysiak et al , 2018.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It was confirmed by our previous study, in which different (R)-and (S)-RA amides and their acetates were synthesized and examined in terms of anticancer and antimicrobial activity. The tested compounds exhibited significant pharmacological potential, and what is more, differences in the activity of the opposite enantiomers were observed in some cases (Matysiak et al 2017(Matysiak et al , 2018.…”
Section: Introductionmentioning
confidence: 92%
“…Limited data on this compound result from the fact that it have not been identified yet in any natural source. However, in 2014 an efficient method for the preparation of (S)-RA was developed (Kula et al 2014), and then, its derivatives were obtained and described for the first time (Matysiak et al 2017(Matysiak et al , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are data that show importance of bioactivity studies on compounds with different chirality. In the studies of Matysiak et al, 15 different antimicrobial activities (against M. flavus ) of ( S )‐ and ( R )‐enantiomer of RA methyl ester were shown. The observed value of MIC in the case of ( S )‐ester was 128 times lower than that of ( R )‐compound.…”
Section: Introductionmentioning
confidence: 97%
“…Fatty acid amides are becoming more and more important in medicinal chemistry due to their biochemical and pharmacological activity, and they are considered as a new family of biologically active lipids 11,12 . First of all, the ability of fatty acid amides to act as antibacterial agents against different microorganisms such as Gram‐negative and Gram‐positive bacteria, yeast, and molds was studied 13–15 . In the studies with Mycobacterium tuberculosis , it was shown that compounds consisting of unsaturated chains with cyclic amines, pyrrolidine, and morpholine were most effective against tuberculosis strains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation